PENERAPAN STORYBOARD DALAM VIDEO IKLAN LAYANAN MASYARAKAT “DIET PLASTIK” - Ferdinanda Ferdinanda; Elianna Gerda Pertiwi (ULTIMART Jurnal Komunikasi Visual, 2020)
Plastic is one material that is often used by humans for various things, such as bags of groceries to food packaging. Plastic is a popular material used in common be- cause it is considered practical. On the other side, plastic also harms the environment if it is not used, because of the nature of the plastic that is difficult to decompose even though it has buried for decades. The increase in plastic waste that sourcing from daily activity needs to address immediately; one of them is through socialization and exposure to the public on the importance of reducing plastic waste. Public Service Announcements (PSA) are quite useful in informing an appeal to the public because they place more emphasis on the public interest that seeks to in-still awareness about the social issues in circulation. PSA can implement through information media such as newspapers, radio, posters to multimedia such as audio-visual media, which are increasingly popular these days due to the rapid development of Information and Communication Technology (ICT). In designing PSA, one of the stages that needs to be done is the creation of storyboards in the pre-production stage. The storyboard contains technical indicators such as picture descriptions, cameras, lighting and supporting properties visualized in the sketch. The suitability and the smooth production of advertisements or cinema are very dependent on the preproduction stage, one of which is the creation of storyboards.